Mapeamento de epítopos baseado em peptídeos na caracterização do anticorpo FabC4 - Alves, Douglas Alexsander (2018)
Phage Display is a molecular technique by which exogenous proteins are expressed on the virus surface. It is an extremely powerful tool to select peptides with specific binding properties from a wide number of variants. Regarding tumors, Phage Display is a promising technology for the selection of targets with clinical relevance, being capable of recognize cancer molecular diversity. Here we describe the characterization of a new FabC4 antibody, made with Phage Display technique, clinically relevant for breast cancer (BC) diagnosis and prognostic purposes. In this study, a bioprospecting assay was done against FabC4 in order to map its epitopes, after using a subtractive selection against an irrelevant Fab, and elution in two steps: with non-malignant proteins, which were discarded, and against BC proteins, which were amplified. By using Phage-ELISA, four of selected clones were able to differentiate serum samples of patients with BC, from serum of patients with benign disease and healthy women. The peptides were chemically synthesized (pA5, pA7, pC4 e pD6) and bound to FabC4. The pC4 demonstrated higher specificity when compared to the others peptides (p<0.05). However, only pD6 peptide was able to differentiate neoplastic samples. Also, we showed for the first time, by immunofluorescence, the cytoplasmic co-localization of annexin A2 (ANXA2) and cytokeratin 10 (CK10) in MDA-MB-231 cell line, suggesting a new molecular behavior of these proteins on triple-negative BC (TNBC). Molecular docking analysis confirmed interactions between FabC4 and the peptides, with better coverage and identity for pC4. This peptide also mimicked ANXA2 and CK10 protein regions that bind to FabC4. Therefore, we described new molecules for the diagnosis of TNBC and our strategy resulted on a successful mapping of FabC4 epitopes, opening new perspectives to better understand and treat TNBC.